2011
DOI: 10.1152/ajpregu.00124.2011
|View full text |Cite
|
Sign up to set email alerts
|

Renal proximal tubule angiotensin AT1A receptors regulate blood pressure

Abstract: All components of the renin angiotensin system necessary for ANG II generation and action have been reported to be present in renal proximal convoluted tubules. Given the close relationship between renal sodium handling and blood pressure regulation, we hypothesized that modulating the action of ANG II specifically in the renal proximal tubules would alter the chronic level of blood pressure. To test this, we used a proximal tubule-specific, androgen-dependent, promoter construct (KAP2) to generate mice with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 38 publications
6
78
0
Order By: Relevance
“…Depletion of endogenous AT 1a receptor in the proximal tubule reduced blood pressure. However, there was no difference in the blood pressure response to a pressor dose of AngII in either experimental model, suggesting that the AT 1a receptor in the renal proximal tubule is a regulator of systemic blood pressure under baseline conditions (Li et al, 2011).…”
Section: Mouse Modelsmentioning
confidence: 75%
“…Depletion of endogenous AT 1a receptor in the proximal tubule reduced blood pressure. However, there was no difference in the blood pressure response to a pressor dose of AngII in either experimental model, suggesting that the AT 1a receptor in the renal proximal tubule is a regulator of systemic blood pressure under baseline conditions (Li et al, 2011).…”
Section: Mouse Modelsmentioning
confidence: 75%
“…These factors combine to cause marked elevations in fluid delivery to the loops of Henle. Furthermore, long-term activation or inhibition of angiotensin II-mediated transport in the proximal tubule can affect BP, presumably through progressive changes of body Na content (71,108).…”
Section: Proximal Nephronmentioning
confidence: 99%
“…For example, we and others have shown that AT 1A receptors in the renal proximal tubule play an important role in Ang II-dependent hypertension by augmenting renal sodium reabsorption through activation of key sodium transporter, including NHE3. 6,7 However, eliminating AT 1A receptors in renal epithelia only partially recapitulated the actions of Ang receptor blockers to abrogate hypertension. Along with kidney epithelia, AT 1 receptors are broadly expressed on the renal vasculature.…”
mentioning
confidence: 99%